2017
DOI: 10.1002/ijc.30593
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to solvents and bladder cancer: A population‐based case control study in Nordic countries

Abstract: The objective of the study was to assess the relationship between exposure to selected solvents and the risk of bladder cancer. This study is based on the Nordic Occupational Cancer (NOCCA) database and comprises 113,343 cases of bladder cancer diagnosed in Finland, Iceland, Norway and Sweden between 1961 and 2005 and 566,715 population controls matched according to country, sex and birth year. Census-based occupational titles of the cases and controls were linked with the job exposure matrix created by the NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1
6

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 27 publications
3
32
1
6
Order By: Relevance
“…The correlation between ageing and cancer is well represented in BC, as with advancing age, the risk of developing BC increases, and patients’ clinical presentation and outcomes worsen [17] . In agreement with previous reports, 86% of all BC cases were aged >50 years [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The correlation between ageing and cancer is well represented in BC, as with advancing age, the risk of developing BC increases, and patients’ clinical presentation and outcomes worsen [17] . In agreement with previous reports, 86% of all BC cases were aged >50 years [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] .…”
Section: Discussionsupporting
confidence: 91%
“…Associated with the risk of BC, Hadkhale et al [7] in 2016 provided an indication of the consequences of work-related contact to trichloroethylene, perchloroethylene, aromatic hydrocarbon solvents, benzene, and toluene. A study performed in an Iranian population with BC and controls, showed a higher risk to BC amongst bus and truck drivers, road construction workers, mechanics, refinery and petrochemical workers, plastic, metal manufacturing, welding, and pipeline workers [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, not all studies adjust for smoking. Agents with a suspected/established role as an occupational bladder carcinogen include 2-naphthylamine, 4-aminobiphenyl, toluene, 4,4'methylenebis(2-chloroaniline), metal working fluids, polyaromatic hydrocarbons (PAH), perchloroethylene, and diesel exhaust [26,27] (Table 2).…”
Section: 2]mentioning
confidence: 99%
“…Farm workers are frequently exposed to pesticides during the preparation and application of these products, or during the cleaning-up of spraying equipment (IARC 2012;Bergman et al 2013;Pecht et al 2018), which might offer a possible explanation for our results. Painters and lacquerers are exposed to a wide variety of solvents during their work, namely toluene, aliphatic and alicyclic hydrocarbons solvents, and aromatic hydrocarbons solvents (Hadkhale et al 2017). Our results should be interpreted with caution as our JEM was not validated by actual measurement data, and JEM-assessed exposure to phthalates for instance is often not corroborated by biological monitoring data among people working as hairdressers and cosmetologists, indicating that individuals involved in these occupations are not necessarily exposed to higher levels of phthalates than the background exposure level (Bonde 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Following Snijder et al's (2002) recommendation, we decided to collapse probable and possible exposures into a single category for our subtype analysis in order to decrease the number of concurrent analyses (Snijder et al 2012). Since van Tongeren's et al's (2002) JEM does not evaluate exposure to solvents, we used the Nordic Occupational Cancer Study's JEM to categorize occupations in regards of possible or probable exposure to the following solvents: aliphatic and alicyclic hydrocarbon solvents, aromatic hydrocarbon solvents, benzene, toluene, chlorinated hydrocarbon solvents, perchloroethylene, 1,1,1 trichloroethane, and trichloroethylene (Hadkhale et al 2017). The evaluation of job titles included in the Hungarian Occupational Exposure System was conducted independently by two of the authors (F-P V, Cs K).…”
Section: Measurementmentioning
confidence: 99%